Performance analysis of resource scheduling in LTE femtocell with hybrid access mode - S. Fouziya Sulthana (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Femtocell is a promising technology that intends in solving the indoor coverage problems so as to enhance the cell capacity. The overall network performance, in turn depends on the access methods used by the femtocells. The access method is used to identify about the user’s connectivity with the femtocell network. There are three access mechanisms defined in Third Generation partnership Project (3GPP) specification for Long Term Evolution (LTE) femtocells: open, closed and hybrid access mechanisms. Hybrid access mechanism is mostly preferred by the network for the effective utilization of resources. But, it is important to regulate the proper scheduling scheme for them. In this paper, scheduling in femtocell is investigated, where, among the non subscribers, preference is given to the users who have high throughput priority metric, thereby increasing overall throughput of the network.